-9-9n=-63

Simple and best practice solution for -9-9n=-63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9-9n=-63 equation:


-9-9n=-63

We simplify the equation to the form, which is simple to understand
-9-9n=-63

We move all terms containing n to the left and all other terms to the right.
-9n=-63+9

We simplify left and right side of the equation.
-9n=-54

We divide both sides of the equation by -9 to get n.
n=6

See similar equations:

| 118=4x+5x+10 | | -12+5y+7q-2y-5q-21= | | 8+5x=-6+30 | | w^2-22w+121=81 | | -138=-6(7-2v) | | -8-3p=-8(1+8p) | | 8x+3x=8x | | n/3+8=14 | | 129-134= | | 3x-15=X | | -5n-3=-58 | | 18-2g=4j | | 7(4-8r)-r=85 | | N+9=4-5 | | 8X-2(X+9)=X+48 | | 2y+1+4y-3=180 | | F(-2)=2x^2-5x+6 | | 42=2n+8 | | 129+134= | | m/4=1.25 | | -129+134= | | -129F+134F= | | -26+10x+12k-3x-4k-18= | | 3-3(2-4a)=-99 | | 2x-1y=-7 | | -3x-3=-6x+27 | | 6-4lnx=0 | | 6(9x+9)+2x= | | 2x-1/2x=12 | | 50x-69=0 | | 3z-13z=70 | | 22=2[b+3] |

Equations solver categories